LES PRATIQUES INFORMELLES DE FINANCEMENT DANS UNE ECONOMIE SOUS BANCARISEE - Chico BOLO NDENDELE; Hortense ANISUNGUDIO KUMBOYO; Kyangambi, Emmanuel Kenya (IJRDO - Journal of Business Management, 2021)
This investigation focuses on informal financing practices in an underbanked economy. The reasons for undertaking this study were to detect the different modes of informal financing and their importantance in an underbanked economy in order to propose some objective guidelines in their decision-making for the satisfaction of the needs of their membres. The results of these surveys have shown that the different modes of informal financing practiced by economic agents in the city of Isiro are : the mutual society commonly called " committee " which représents 76 % of surveys, the tontine or "likelemba" is équivalent to 08 % inquiries,hoarding accounts for 12% of inquiries and borrowing from third parties has only 04 % inquiries. The most widely uses informal funding method currently in Isiro is the "Committee" or mutual representing 76 % of inquiries given its socio-economic and humanitarian benefits for its practitioners and its scale in the city of Isiro. In addition,the under-banking of the city of Isiro has a negative impact on the expansion of economic activities because these different modes of informal financing fail to meet the overall financing needs of Isiro’s economic agents. Indeed, 38% of surveys state that their satisfaction with informal financing ranges between 30 to 39%, 28% of surveys estimate that their satisfaction ranges between 20 to 29% and 12% have a degree of satisfaction between 40 and 49%. Thus,74% of surveys state that their level of satisfaction from informaly financing is average,6% have a high level of satisfaction and only 20% have acknowledged having low satisfaction with informal financing.